2013
DOI: 10.1186/gb-2013-14-12-r148
|View full text |Cite
|
Sign up to set email alerts
|

Co-binding by YY1 identifies the transcriptionally active, highly conserved set of CTCF-bound regions in primate genomes

Abstract: BackgroundThe genomic binding of CTCF is highly conserved across mammals, but the mechanisms that underlie its stability are poorly understood. One transcription factor known to functionally interact with CTCF in the context of X-chromosome inactivation is the ubiquitously expressed YY1. Because combinatorial transcription factor binding can contribute to the evolutionary stabilization of regulatory regions, we tested whether YY1 and CTCF co-binding could in part account for conservation of CTCF binding.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 97 publications
5
76
0
1
Order By: Relevance
“…To determine whether it actually was an active TFBS, we looked for overlapping regions with the ubiquitous TF CTCF, and with active transcription marks H3Kme3 and Pol II. As previously reported in more detail in [40] , YY1 co-bound with CTCF in a great extent in the human genome, and they show a significant genome-wide interaction across species, which suggests a heavy association through evolution. YY1-CTCF co-bound regions are also frequently related to Pol II and H3Kme3 histone marks, as well as to CpG islands at active transcription sites [40] .…”
Section: Discussionsupporting
confidence: 72%
“…To determine whether it actually was an active TFBS, we looked for overlapping regions with the ubiquitous TF CTCF, and with active transcription marks H3Kme3 and Pol II. As previously reported in more detail in [40] , YY1 co-bound with CTCF in a great extent in the human genome, and they show a significant genome-wide interaction across species, which suggests a heavy association through evolution. YY1-CTCF co-bound regions are also frequently related to Pol II and H3Kme3 histone marks, as well as to CpG islands at active transcription sites [40] .…”
Section: Discussionsupporting
confidence: 72%
“…In agreement with this idea, Ruan and colleagues reported evidence that CTCF-mediated looping interactions might function to coordinate nearby interactions involving RNA Pol II . Furthermore, a recent genomics analysis showed that up to 30% of YY1 sites bind at locations directly adjacent to CTCF and might work together to cooperatively influence occupancy (Schwalie et al 2013). Thus we posit that architectural proteins such as YY1 might cooperatively build upon a constitutive CTCF architectural "seed" scaffold to connect nearby developmentally regulated genes and enhancers.…”
Section: Wwwgenomeorgmentioning
confidence: 99%
“…4A; Supplemental Methods SM1.11). In addition, we used a previously published data set to identify CTCF genome-wide binding in immortalized lymphoblast cells from four primate species (Schwalie et al 2013). We found between ∼24,000 and 48,000 CTCF binding sites across the four Muridae species and between ∼21,000 and 57,000 across the four Hominidae species (Supplemental Fig.…”
Section: Retrotransposition Of Sine B2_mm1 Elements Drove a Species-smentioning
confidence: 99%
“…The paired-end libraries were sequenced at 100 bp on the HiSeq2000 platform. In addition, the data set from Schwalie et al (2013) was used to identify the CTCF binding sites in primates. Sequencing reads were aligned to the appropriate reference genome using Bowtie 2 version 2.2.6 (Langmead and Salzberg 2012).…”
Section: Ctcf Binding Site Analysismentioning
confidence: 99%
See 1 more Smart Citation